RELIGIOUS ORIENTATION AND WHISTLEBLOWING INTENTION: UNPACKING THE MOTIVATIONAL ROLE OF PUBLIC SERVICE MOTIVATION - Risya Khaerun Nisa; Irsyadunnas (STABILITY : Journal of Management and Business, 2025)
High-profile accounting scandals have renewed global attention to the mechanisms that encourage professionals to report wrongdoing, particularly in roles entrusted with safeguarding the public interest. This study investigates how intrinsic and extrinsic religious orientations influence external whistleblowing intention among professional accountants and examines the mediating role of public service motivation (PSM). Drawing on Self-Determination Theory (SDT), the study proposes that religious orientation affects ethical behavior not directly, but through its impact on autonomous, value-driven motivation. Using a cross-sectional survey of 359 accountants in Indonesia, the study tested a structural model linking religious orientations, PSM, and whistleblowing intention. The results indicate that intrinsic and extrinsic religious orientations do not directly affect whistleblowing intention. Instead, intrinsic orientation strengthens PSM, extrinsic orientation weakens it, and higher PSM increases external whistleblowing intention, mediating both relationships.The study contributes theoretically by integrating SDT with whistleblowing research and demonstrating the central role of autonomous motivation in shaping ethical reporting behavior. The findings highlight the importance of public-service-oriented values in strengthening moral courage and societal commitment.